Controllable Formation of the Crystalline Phases in Ge–Ga–S Chalcogenide Glass‐Ceramics. Issue 1 (12th September 2016) - Yang, Xinyu; Zhang, Mingjie; Yan, Kunlun; Han, Liyuan; Xu, Qin; Liu, Haitao; Wang, Rongping
Abstract : We prepared chemically stoichiometric, S‐poor and S‐rich Ge–Ga–S glasses and annealed them at a temperature that was 20°C higher than its respective glass transition temperature. We aimed at tuning the formation of the different crystals in chalcogenide glass‐ceramics. Through systematic characterization of the structure using X‐ray diffraction and Raman scattering spectra, we found that, GeS2 and GeS crystals only can be created in S‐rich and S‐poor glass‐ceramics, respectively, while all GeS, Ga2 S3, and GeS2 crystals exist in chemically stoichiometric glass‐ceramics. Moreover, we demonstrated the homogeneous distribution of the crystals can be formed in the S‐rich glass‐ceramics from the surface to the interior via composition designing. The present approach blazes a new path to control the growth of the different crystals in chalcogenide glass‐ceramics.